Insights into the potential dependence of the borohydride electrooxidation reaction mechanism on platinum nanoparticles supported on ordered carbon nanomaterials. (10th October 2015) - Olu, Pierre-Yves; Bonnefont, Antoine; Rouhet, Marlène; Bozdech, Sébastien; Job, Nathalie; Chatenet, Marian; Savinova, Elena
Abstract : Graphical abstract: Abstract : Highlights: Pt/VACNF active layers of different Pt site densities were prepared. Their activity towards borohydride oxidation reaction was characterized. The low-potential activity depends on the Pt site density, due to BHx, ad poisoning. OHad in PtOx region remove the poisoning (Langmuir-Hinshelwood stripping of BHx, ad ). The whole reaction mechanism was modelled using a mean-field microkinetics model. Abstract: Borohydride oxidation reaction (BOR) was studied on platinum nanoparticles deposited on vertically-aligned carbon nanofilaments (VACNF). Depending on the amount of Pt deposited on the VACNF support, Pt/VACNF electrodes with a wide range of Pt nanoparticle density on the VACNF substrate were obtained. Cyclic voltammetries of BOR on these model Pt/VACNF electrodes using the rotating disk electrode (RDE) setup demonstrated the existence of two different and potential-dependent pathways for the BOR on such nanostructured Pt surfaces. The low potential BOR pathway ( E < 0.55 V vs. RHE) does not occur (in near-steady-state conditions) when the Pt nanoparticle density of the Pt/VACNF electrode is too low, pointing out to the sensitivity of the low-potential BOR towards the density of free Pt sites. The complete dissociative adsorption of BH 4 −, a reaction strongly demanding for free Pt sites, was proposed as the first step of the BOR, in agreement with recent DFT and experimental studies. At higher potential values ( E > 0.55 V vs. RHE), this influence of the Pt site density levels off, mainly due to the dual role of hydroxyl species adsorbed on the Pt surface. Indeed, while reducing the fraction of free Pt sites, adsorbed hydroxyls also accelerate the removal of the stable BOR adsorbed intermediates that block the Pt surface (and are responsible for the sensitivity of the low-potential BOR towards the density of free Pt sites) by a Langmuir-Hinshelwood type electrooxidation. In the meantime, voltammograms plotted using an Au-ring rotating ring-disk electrode (RRDE) specifically enabled the detection of BH3 OH − released in this potential region at the Pt/VACNF disk electrode. The first steps of this high-potential BOR pathway, including the Pt-oxides formation, were proposed. The whole tentative BOR mechanism has been discussed using a mean field microkinetic model, where experimental variation of Pt nanoparticle density has been modelled by a variation of Pt site density. The main features of the Au-ring RRDE experiments are qualitatively reproduced.